2004
DOI: 10.1212/01.wnl.0000140255.63532.28
|View full text |Cite
|
Sign up to set email alerts
|

The neurology resident as teacher

Abstract: Abstract-There is a need to improve the quality of teaching done by neurology residents because neurology residents are intimately involved in medical student education. This article reviews the available literature on techniques to improve the teaching ability of resident physicians. Eight randomized prospective studies were identified from health and education databases. The outcomes measured were student ratings of residents or objective ratings of interactions between residents and students. The skills cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
0
16
0
7
Order By: Relevance
“…Seventeen competencies with associated methods of assessment were identified, as outlined in Table 2. The methods used to identify competencies of preceptors included expert opinion based on literature reviews and qualitative synthesis (8,9,11,60,61) , Delphi approaches (10,29,32) , and qualitative studies examining the qualities of preceptors that preceptees value most (27,37,42,44,45,51) . Fifteen studies identified competencies, but assessment had not been implemented or reported (8-11, 27, 29, 32, 37, 38, 41, 45, 48, 56, 58, 60) , with only four studies detailing performance indicators for the competencies described (8)(9)(10)(11) .…”
Section: Competencies and Methods Of Assessment Of Preceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen competencies with associated methods of assessment were identified, as outlined in Table 2. The methods used to identify competencies of preceptors included expert opinion based on literature reviews and qualitative synthesis (8,9,11,60,61) , Delphi approaches (10,29,32) , and qualitative studies examining the qualities of preceptors that preceptees value most (27,37,42,44,45,51) . Fifteen studies identified competencies, but assessment had not been implemented or reported (8-11, 27, 29, 32, 37, 38, 41, 45, 48, 56, 58, 60) , with only four studies detailing performance indicators for the competencies described (8)(9)(10)(11) .…”
Section: Competencies and Methods Of Assessment Of Preceptorsmentioning
confidence: 99%
“…The competencies being measured and the mode of measurement also needs to be aligned. Gill (2004) notes that the ultimate goal would be to link preceptor performance and preceptee learning (61) . Whilst Griffith (2000) linked preceptee performance in an exam with perceived preceptor quality, the competencies that led to those preceptors being rated highly were not detailed (39) .…”
Section: Moderatementioning
confidence: 99%
“…Seventeen competencies with associated methods of assessment were identified, as outlined in Table 2. The methods used to identify competencies of preceptors included expert opinion based on literature reviews and qualitative synthesis (5,6,8,57,58) , Delphi approaches (7,26,29) , and qualitative studies examining the qualities of preceptors that preceptees value most (24,34,39,41,42,48) . Fifteen studies identified competencies, but assessment had not been implemented or reported (5-8, 24, 26, 29, 34, 35, 38, 42, 45, 53, 55, 57) , with only four studies detailing performance indicators for the competencies described (5)(6)(7)(8) .…”
Section: Competencies and Methods Of Assessment Of Preceptorsmentioning
confidence: 99%
“…Residencies need to incorporate more teaching programs to train residents in these important skills. 20 Self-determination theory argues that measures that stimulate intrinsic sources of motivation to learn are more effective than measures that control motivation through regulations and requirements. 21 Restructuring the culture and learning environment to satisfy the basic psychological need for autonomy and competence among residents should further enhance motivation to learn.…”
Section: Dealing With This Challengementioning
confidence: 99%